A critical review on thermal management technologies for motors in electric cars. (25th January 2022) - Wang, X.; Li, B.; Gerada, D.; Huang, K.; Stone, I.; Worrall, S.; Yan, Y.
Highlights: Advanced thermal management technologies for motors in electric cars are reviewed. Air and liquid cooling methods for stator, winding and rotor were critically examined. Possible methods to enhance the heat conduction in motors are thoroughly evaluated. Pros and cons of current studies are presented, with suggestions for future work. Abstract: The development of electric cars has well been regarded as a major solution for tackling the challenges of carbon-neutrality faced by the modern communities. Electric motor is certainly the core and most important components of an electric car, and the thermal management for electric motors has drawn increasing attention from both industry and academic society. This is because electric motors in modern electric cars are required to be more powerful and competitive with higher torque, higher speed and higher power density, therefore the efficient thermal management has become essential to maintain the motors efficiency, durability and safety. The failure of thermal management will result in demagnetization of magnets, aging of the insulation materials, decrease of efficiency, shorter lifetime and even burnout of motors. To enlighten the future research, in this paper, both the theoretical modeling and experimental investigations of the latest thermal management methods are reviewed. The state-of-the-art of various thermal management techniques, including air cooling (natural and forced air cooling, air impingement cooling) and liquid cooling (water/oil jacket cooling, jet impingement cooling, spray cooling, immersion cooling, slot channel forced convection cooling) for the stator, winding and rotor are critically presented. Meanwhile, heat transfer enhancement methods by conduction based on potting materials, thermal paste, heat guides, PCMs and heat pipes are highlighted. Following that, hybrid thermal management technologies to address extreme conditions are also discussed. In the last section, some suggestions are given for future possible research and applications. The paper is expected to be a good reference and inspiration for the development of new thermal management concepts of electric motors.